Sodium arsenite induces islets β-cells apoptosis and dysfunction via SET-Rac1-mediated cytoskeleton disturbance - Tianming Qiu; Yu Zhi; Jingyuan Zhang; Ningning Wang; Xiaofeng Yao; Guang Yang; Liping Jiang; Li Lv; Xiance Sun (Ecotoxicology and Environmental Safety)
Sodium arsenite (NaAsO2), the most common form of inorganic arsenic prevalent in the environment, has been closely linked to islet β-cell dysfunction, a critical pathological hallmark of type 2 diabetes (T2D). Even though apoptosis plays a pivotal role in arsenic-induced islet β-cell dysfunction, the explicit underlying mechanisms remain elusive. Here, we have identified that the SET-Rac1 signaling pathway is instrumental in the apoptosis and dysfunction of islet β-cells induced by NaAsO2. During NaAsO2-induced islet β-cell apoptosis and dysfunction, our observations indicated downregulation of SET (almost 0.5-fold) and upregulation of Rac1 (0.5-fold). Notably, overexpression of SET or inhibition of Rac1 substantially mitigated the apoptosis of islet β-cells and ameliorated the impaired insulin secretion (increased from 0.1 ng/ml to 0.2 ng/ml) caused by NaAsO2 exposure. In addition, we detected cytoskeletal disorganization following NaAsO2 treatment, characterized by elevated Cofilin-1 protein expression (approximately 2.5-fold) and disrupted cytoskeleton arrangement. Significantly, overexpression of SET or deletion of Rac1 rectified the NaAsO2-induced cytoskeletal abnormalities, as evidenced by the reduced Cofilin-1 expression and enhanced F-actin fluorescence. Our research delineates that NaAsO2 triggers apoptosis and functional impairment of islet β-cells through cytoskeletal rearrangement mediated by the SET-Rac1 pathway. This discovery could provide novel insights into therapeutic strategies for T2D provoked by environmental toxicants.